(untitled) (Agro Productividad, 2021)
Objective: To describe the sequential pattern of reproductive development of Medicago sativa L. (flowering dynamic) using the relation between principal floral stem nodes and accumulated growing degree day (GDD) in different environmental conditions, and to determine the use of this relationship as a predictor of the seed harvesting date. Design/Methodology/Approach: It was carried out in random blocks and factorial arrangement of 2?5, with two repetitions. Each repetition was made up of 30 plants. Results: The flowering dynamic followed the same pattern between varieties, with a linear relation between GDD and number of floral nodes. The year A0 was different from the years A1 and A2. Therefore, A1 with cutting, and A2 with and without cutting presented less GDD during the flowering stage. In contrast, A0 showed more GDD during this period. In the different environmental conditions, the linear curves of flowering dynamic turned erratic after the tenth floral node (300 GDD) due to a low rate of plants with more than 10 floral nodes along the principal stem. Study Limitations/Implications: It is necessary to have a meteorological station near the alfalfa seed production site, in order to specify the GDD required for predicting the correct moment to harvest seeds. Findings/Conclusions: The reproductive development of M. sativa presents a linear relation between the number of floral nodes and GDD, which allows the prediction of the optimal seed harvesting date, in any environmental condition present.